AMMONITE ZONATION AND INTERREGIONAL CORRELATION OF THE INDUAN STAGE - Shevyrev A.A. (My University, 2001)
The central Himalayas and the Salt Range are type areas of the lower and upper Induan substages, respectively. The lower Induan Substage spans the interval of Otoceras and Ophiceras beds. The Otoceras Beds in the range of concavum and boreale zones are most complete in the Boreal region. The woodwardi Zone representing the basal Triassic unit in the Tethyan region corresponds to an upper part of the boreale Zone coupled with a basal portion of the Ophiceras Beds of the Boreal region. The upper Induan Substage begins at the appearance level of meekoceratids, the first Triassic ammonoids having a flattened ventral side. This level is easily traceable in the Tethyan and Boreal sections. The upper Induan boundary is recognizable within lower horizons of the Ceratite Sandstone (basal portion of flemingianus Zone) and at the base of the hedenstroemi Zone of the Boreal region. The Induan ammonite successions of central Himalayas, Kashmir, Nepal, Salt Range, Arctic Canada, and Siberia are described, and a scheme of their zonal correlation is suggested.
Keywords: Induan; Triassic; Мезозой::Триасовая; Мезозой::Триасовая::Нижний::Индский; Mesozoic::Triassic; Mesozoic::Triassic::Lower::Induan